Numerical derivation of averaged material properties of hollow concrete block masonry - Wu, C.; Hao, Hong (Pergamon, 2008)
The homogenization technique has been used to derive equivalent material properties of masonry units for many years. However, most previous research work has concentrated on the derivation of equivalent material properties of a solid brick masonry structure. Very few studies have been conducted to investigate the complex mechanical properties of a hollow concrete block masonry unit. In this paper, numerical simulations of laboratory tests are conducted to derive the equivalent material properties of a three-dimensional basic cell of hollow concrete block masonry. A double scalar damage model based on the concept of continuum damage mechanics is applied to modeling the failure of mortar joint and concrete. In the numerical model of the basic cell, the hollow concrete block and mortar with their nonlinear material properties are modeled in detail. By applying various displacement boundaries to the basic cell surfaces to simulate the displacement-controlled laboratory tests, the averaged stress and strain of the basic cell under different stress states are derived numerically. The homogenized or equivalent material properties of the hollow concrete masonry are determined from the averaged stress and strain relations of the basic cell. To check the validity of the derived equivalent material properties, the dynamic response and damage of a hollow concrete masonry panel subjected to airblast loading is modeled with the equivalent material properties or with the distinctive mortar and brick properties. The efficiency and accuracy of using the derived equivalent material properties in numerical modeling of hollow concrete brick masonry are demonstrated.